2007
DOI: 10.1210/en.2006-1289
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mechanical Stretch on Cyclooxygenase Type 2 Expression and Activator Protein-1 and Nuclear Factor-κB Activity in Human Amnion Cells

Abstract: Stretch of the uterus plays a role in parturition. Uterine stretch also leads to stretch of the fetal membranes, including the amnion, an important source of prostaglandin E2 (PGE2). We tested the hypothesis that stretch of the amnion leads to increased cyclooxygenase (COX)-2 expression and PGE2 synthesis and investigated the mechanisms involved. We obtained amnion from women undergoing term elective cesarean section and isolated amnion epithelial cells. These cells were subjected to 11% static stretch. Stretc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 37 publications
2
44
0
Order By: Relevance
“…As shown in Figure I, mechanical stretch also significantly increased NF-B transcriptional activity (4.0Ϯ0.6-fold vs control; without mechanical stretch; nϭ4), consistent with other reports. 19,20 The effect of mechanical stretch on activation of both Egr-1 and NF-B is specific because mechanical stretch did not increase other transcriptional factor activity. Next, we examined if Egr-1 regulates IGF-1R expression in vein grafts when mechanical stretch is high.…”
Section: Egr-1 Is Involved In Mechanical Stretch-stimulated Igf-1r Trmentioning
confidence: 99%
“…As shown in Figure I, mechanical stretch also significantly increased NF-B transcriptional activity (4.0Ϯ0.6-fold vs control; without mechanical stretch; nϭ4), consistent with other reports. 19,20 The effect of mechanical stretch on activation of both Egr-1 and NF-B is specific because mechanical stretch did not increase other transcriptional factor activity. Next, we examined if Egr-1 regulates IGF-1R expression in vein grafts when mechanical stretch is high.…”
Section: Egr-1 Is Involved In Mechanical Stretch-stimulated Igf-1r Trmentioning
confidence: 99%
“…Increased PG synthesis occurs first in the region overlying the cervix where it is thought to mediate cervical ripening and dilation. Mechanical stretch of human amnion epithelial cells has been shown to lead to the activation of AP-1 and NF-κB systems and in turn, increase COX-2 and PG expression [47]. PGs have been shown to play a role in placental separation M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT [48], fetal membrane rupture by inducing matrix metalloproteinase (MMP) activity [49], and promoting myometrial contractility.…”
Section: Inflammationmentioning
confidence: 99%
“…Inflammatory mediators such as interleukin-1b (IL-1b), tumor necrosis factor-a (TNF-a), and prostaglandin E 2 (PGE 2 ) have been detected in synovial fluid samples from patients with joint disorders [4][5][6]. In addition, Mohan et al [7] reported that mechanical stretch induced the expression of cyclooxygenase-2 (COX-2) during the biochemical events involved in parturition, which resemble inflammatory reactions.…”
Section: Introductionmentioning
confidence: 99%